PENGARUH EXPERIENTAL MARKETING DAN EXPERIENTAL VALUE TERHADAP COSTUMER SATISFACTION PADA PENGGUNA HANDPHONE REDMI DI SMK NEGERI 03 BENGKULU SELATAN - Herfianti, Meiffa; Fransisco, Lee (Universitas Prof. Dr. Hazairin SH, 2023)
This study aims to determine the effect of Experiential Marketing and Experiential Value on Customer Statistics on Redmi mobile users at SMK Negeri 03 Bengkulu Selatan. This study used a quantitative method with a Likert scale (questionnaire). The number of respondents in this research was 105 people. iMethod of data collection iusing a questionnaire. The analysis technique uses multiple linear regression analysis tests, the coefficient of determination (R2) and hypotheses tests, namely the it test and the if test. The results of this study indicate that partially the experiential marketing variable has a significant effect on the customer satisfaction variable and the experiential value variable has a significant effect on the customer satisfaction variable. Simultaneously, it shows that the experiential marketing and experiential value variables simultaneously have a significant effect on customer satisfaction. The limitations of this study are using data in the form of respondents' answers to the statements submitted on the research questionnaire. Respondents who filled out the questionnaire at random and did not pay close attention to each statement. It is hoped that the indicators described in this study can be used as a reference for Redmi products, especially Redmi product sellers in South Bengkulu, in increasing the experience marketing of their customers and increasing the experience value in in-store transaction life.